In Silico Evaluation of the Glioma Activity of Reported Compounds from the Extract Rhodomyrtus tomentosa (Aiton) Hassk.) - Marwati Marwati; Gemini Alam; Risfah Yulianty; Fitriyanti J. Sami; Syamsu Nur; Nursamsiar; Yusnita Rifai (Jurnal Penelitian Pendidikan IPA, 2025)
The plant Rhodomyrtus tomentosa is empirically treated and can be developed in vitro as an anticancer. To see the interaction and evaluate the compound of Rhodomyrtus tomentosa as glioma inhibition, especially on Smoothened receptor by using the in silico. 44 compounds from Rhodomyrtus tomentosa leaf plants obtained from previous studies and native ligands and target proteins were generated through PubChem and RSCB protein database. In silico analysis was performed using various, absorption, distribution, toxicity prediction, and molecular tethering of compounds to smoothened (SMO) target proteins. Drug similarity showed that most of the compounds conformed to Lipinski's rule. The absorption and Distribution analysis of the compounds for each parameter gave different pharmacokinetic profiles according to the physicochemical properties of the compounds. Quercetin, β-sitosterol, and Quercetrin are prediction mutagenic, and Rhodomyrtoxin C and β-amyrenonol compounds are What follows is a prediction genotoxic carcinogenic. The results of docking analysis showed that the leaf compounds of Rhodomyrtus tomentosa leaf compounds that can interact with SMO receptors with the best interaction shown by compound 13 (Rhodomyrtoxin C) with a free bond energy of -9.29 kcal/mol, Quercitrin of-12.72 kcal/mol, 2-(4-hydroxyphenyl)acetic acid -14.24 kcal/mol and β-Sitosterol of -11,61 kcal/mol and has the same key amino acid residues as the native ligand LY2940680 (4-fluro-N-methyl-N-{1-[4-(1-methyl-1H-pyrazol-5-yl)phthalazine-1yl]piperidin-4-yl} 2 (trifluoromethyl) benzamide )namely Arg400, Asp473 and Glu518. His470, and Asn521. Specific compounds from Rhodomyrtus tomentosa are predicted to be developed as candidates for glioma inhibitors predicted to have the same mechanism of action as Smoothened inhibitors and further research is needed.